MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MENGANYAM ANAK USIA 5-6 TAHUN DI RA AL FURQON DESA KOTO PERAMBAHAN KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Elvida, Elvida; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in motor skills fine motor skills in children aged 5-6 years through weaving In Ra Al Furqon Koto Perambahan Village East Kampar District Regency Of Kampar. This study is the kind of research that uses classroom action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. The subjects were children aged 5-6 years were 10 children in RA Al-Furqan. The research data obtained through observation and data analysis with quantitative descriptive analysis techniques of fine motor skills in children aged 5-6 years. It can be seen from the increase in the average percentage of fine motor skills in the first cycle of 54.79% which are in developing criteria to expectations (BSH) and an increase of 43.37% in the second cycle be 78.54% which is at criteria developed very well (BSH). So, weaving can improve fine motor skills of children aged 5-6 years in RA Al-Furqan Koto village Encroachment Kampar District Kampar regency.Keywords: Fine Motor Skill, weaving